Probing the non-thermal physics of stellar bow shocks using radio observations - Martinez, Javier Rodrigo (2023)
Context. Massive runaway stars produce bow shocks in the interstellar medium. Recent observations revealed radio emission from a few of these objects, but the origin of this radiation remains poorly understood. Aims: We aim to interpret this radio emission and assess under which conditions it could be either thermal (free-free) or non-thermal (synchrotron), and how to use the observational data to infer physical properties of the bow shocks. Methods: We used an extended non-thermal emission model for stellar bow shocks for which we incorporated a consistent calculation of the thermal emission from the forward shock. We fitted this model to the available radio data (spectral and intensity maps), including largely unexplored data at low frequencies. In addition, we used a simplified one-zone model to estimate the gamma-ray emission from particles escaping the bow shocks. Results: We can only explain the radio data from the best sampled systems (BD+43°3654 and BD+60°2522) assuming a hard electron energy distribution below ∼1 GeV, a high efficiency of conversion of (shocked) wind kinetic power into relativistic electrons (∼1 − 5%), and a relatively high magnetic-to-thermal pressure ratio of ηB ∼ 0.2. In the other systems, the interpretation of the observed flux density is more ambiguous, although a non-thermal scenario is also favoured. We also show how complementary observations at other frequencies can allow us to place stronger constraints in the model. We also estimated the gamma-ray fluxes from the HII regions around the bow shocks of BD+43°3654 and BD+60°2522, and obtained luminosities at GeV energies of ∼1033 erg s−1 and 1032 erg s−1, respectively, under reasonable assumptions. Conclusions: Stellar bow shocks can potentially be very efficient particle accelerators. This work provides multi-wavelength predictions of their emission and demonstrates the key role of low-frequency radio observations in unveiling particle acceleration processes. The prospects of detections with next-generation observatories such as SKA and ngVLA are very promising. Finally, BD+43°3654 may be detected in GeV in the near future, while bow shocks in general may turn out to be non-negligible sources of (at least leptonic) low-energy cosmic rays.